Business Challenges for Transitioning from Web2 Ecosystems to Web3 Ecosystems - Kunjumuhammed, Bilal (Digital Repository of Theses, 2025)
Background: The transition from Web2 to Web3 ecosystems presents several business challenges. Web3 is being touted as the future of the internet, with a vision for a new, blockchain-based web that includes cryptocurrencies, NFTs, DAOs, decentralized finance, and more. The current Web2 to Web3 transition framework focuses more on the technical audience. This study aims to create a Web2 to Web3 business transition framework for helping business owners, Product Managers, Management consultants, etc. Methods: In this investigation, an analysis is performed on the whitepapers and official documentation of fifty well-known decentralized applications (DApps) and publicly accessible business case studies, utilizing quantitative and qualitative methods (Mixed method). A literature review was conducted to uncover recurring patterns and issues. Secondary sources will be utilized to gather the necessary data. Results: As part of our study, we will be analyzing 50 decentralized applications (DApps) that are relevant to business audiences, such as business owners, management consultants, and strategists. We aim to create a Web2 to Web3 Enterprise transition framework to help businesses prepare to shift to Web3 ecosystems. Using a mixed-method approach to gather data and identify recurring patterns, we hope to provide insights into the challenges and opportunities of Web3. This framework will be based on our analysis of DApp whitepapers, official documents, and business case studies. It will be designed to help businesses navigate the transition to Web3 with confidence and clarity. Discussion and Conclusion: The transition from Web2 to Web3 ecosystems presents several business challenges. However, understanding this new digital wave’s core features and the potential disruption it could bring remains important for business leaders in a wide range of sectors. Further research is needed to fully understand this transition’s implications and develop strategies for managing the associated risks.